Creación de una empresa contable con servicios al sector empresarial, comercial, agrícola y otros en el cantón el Empalme - Rodríguez Cedeño, Jennifer Vanessa (2011)
Quevedo In the canton there are different national and international companies that sell name brand products with different flavors of jams, is to indicate that there Quevedo a processing company that offers type of banana jam home. This study aims to analyze the economic and financial feasibility of installing a processing plant banana compote. To fulfill this objective, has analyzed the current market situation the same as has been shown that due to population increase reflected an unmet demand. The launch of the products, will in the Four-Beam, as a significant area in the population aspect also seeks to satisfy unmet demand side of the market in four sets. This investment project proved to be technically and economically feasible, because the five-year projections, with reference to an interest rate of 9% applied to capital and a discount rate of 13% with an average inflation of 4%, capital own 30% and 70% paid, which results in a Net Present Value (NPV) positive $ 32,419.39. The initial investment amounts to a total of $ 14,708.8 This includes the establishment of more fixed investment growing, they are recovered over a period of 2 years. With regard to financial analysis, with its most representative parameter is the Internal Rate of Return (IRR) is spewing a result of 19.11%, being 13% higher than the opportunity rate applied to the project, indicating that the it is profitable. Cost benefit ratio (RB / C) gave a result greater than 1.47 unit indicating that an investment is feasible. This analysis allows us to deduce that the investment to produce jams banana 8 ounces, projected annually which is expected to be made by entrepreneurs who have access to technology and credit then. These projects constitute a large source of employment for the people of Canton and its hinterland